Theodicy and Honesty - Wood , Allen W.; Norman Halls , Ruth (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This study examines Immanuel Kant’s 1791 essay on theodicy as a legal proceeding before the “court of reason,” where divine justice is assessed through rational inquiry rather than doctrinal authority. It explores the political context of the essay, Kant’s interpretation of nature, and the role of the Book of Job as a model of sincere religious faith. The study also considers the duties of theologians and clergy and reflects on the essay’s continuing relevance for issues related to religion, morality, and the problem of evil.